Five brigade atrocities in Zimbabwe: categorising international crimes and evaluating the criminal liability of perpetrators - Malunga, Siphosami Patrick (University of the Witwatersrand, Johannesburg, 2023)
In virtually every village in the Zimbabwean provinces of Matabeleland and parts of Midlands, there are reminders of heinous atrocities perpetrated against defenceless civilians by the government between 1982 and 1987. These atrocities, commonly known as the ‘Gukurahundi,’ a moniker for the army brigade that committed them, resulted in the deaths of an estimated 20 000 Ndebele civilians. Many of those killed were abducted and forcibly disappeared, and their bodies thrown into mine shafts or buried secretly in shallow graves. Others were publicly executed and buried in mass graves. Thousands more were starved, tortured, raped, unlawfully detained, and their homes and belongings destroyed during the Gukurahundi operation. Survivors continue to bear physical, emotional and psychological scars while alleged high- level perpetrators continue to rely on their political incumbency to enjoy impunity and remain shielded from accountability for their crimes. This doctoral thesis addresses the existing literature gap on the legal classification of the Gukurahundi atrocities. It seeks to determine whether atrocities committed by Five Brigade of the Zimbabwe National Army (ZNA) and other security agencies against civilians constitute international crimes of genocide, crimes against humanity and war crimes. It assesses the application of international criminal andhumanitarian law in Zimbabwe and investigates the status of the Matabeleland Conflict under international humanitarian law. Further, it explores whether alleged perpetrators can be held individually criminally responsible for Gukurahundi atrocities under international law. Finally, the thesis is expected to contribute to understanding the legal nature of Gukurahundi atrocities, the role of alleged perpetrators and the victims’ prospects for justice and accountability
A thesis submitted in fulfillment of the requirements for the degree Doctor of Philosophy in the Faculty of Law of the University of Witwatersrand, University of the Witwatersrand, Johannesburg, 2023
Keywords: Gukurahundi atrocities; Zimbabwe; International crimes; Genocide; Crimes against humanity; Individual criminal responsibility; War crime; Accountability; UCTD; SDG-16: Peace, justice and strong institutions